A nova comunicação do corpo cristão: a transformação da imagem do corpo sagrado na mídia - Salles, Paula Francisco (2014)
In recent decades, in some Christian communities a very curious phenomenon has occurred, which has intensified and relates to a profound transformation in the image of the body of evangelical Christians. The first hypothesis proposes that the body must have acquired permission to exist in Christian churches through dance and the Christian dance groups proliferated so much that eventually there is a need to import the format of festivals and exhibitions. To this sums up a sub-hypothesis that dance is an adaptive strategy of Puritan conservative discourse, a result of gospel culture derived from neoliberalism. In this context, it has become essential to produce images of the body for dissemination in media outlets. The object of this research is the role of dance in transforming the image of the Christian Protestant body and the dissemination of the new image in the media and the changes in communication mechanisms in both church and society. This research, of theoretical and practical nature, joined both bibliographical and work on the field, watching the group Gospel Group Free to Dance, Gospel Group Free to Dance, Ministry of Dance of the Reborn in Christ Church from Osasco, Gospel Dance Festival Abba Dance 2013 and III Seminar Marks of the Dance Widening Tents, realized in Maua. A collection of promotional material was also gathered with dance groups from other Protestant churches in order to determine possible identity of the singularities within the diversity environment. The literature review focused mainly on Corpomídia Theory KATZ & GREINER, which proposes the body in co-dependence with the environment, and with it, read the body transformation undergone by the Christian body in progress. Once the image becomes central to this investigation, the study of DAMASIO on the concept of image as a synonym of mapping, done by the brain on patterns external to it. To understand what is here identified as ‗Christian body , collaborated CUNHA; GOMES; MENDONÇA; MENDONÇA & VELASQUES FILHO; and ALVES. Finally to investigate the expression of dance in evangelical churches contributed COIMBRA; and GUALBERTO